Chitosan grafted SiO2-Fe3O4 nanoparticles for removal of antibiotics from water - KERKEZ KUYUMCU, ÖZGE (SPRINGER HEIDELBERG, 2018)
The antibiotic wastes in environment are very dangerous for human being because of the spread of epidemics due to increasing of the antibiotic-resistant bacteria. For reducing the proliferation of these bacteria, an environmental-friendly, cheap and non-toxic adsorbent, chitosan-grafted SiO2/Fe3O4, was developed in this study. The chitosan-grafted SiO2/Fe3O4 (Chi-SiO2/Fe3O4) nanoparticles were prepared and characterised by different physical and chemical techniques such as X-ray diffraction spectroscopy (XRD), Fourier transform infrared spectroscopy (FTIR), N-2 adsorption-desorption isotherms (BET), thermogravimetric analysis (TGA), vibrating sample magnetometer (VSM), scanning electron microscopy (SEM) and zeta-potential analysis. The prepared nanoparticles were used for ciprofloxacin (CPX) adsorption from water. The nonlinear Langmuir and Freundlich isotherms were applied to experimental data. And Langmuir isotherm showed the best fit. The nonlinear pseudo-first-order and pseudo-second-order kinetic models and Weber-Morris intraparticle diffusion model were applied to kinetic data. The adsorption process followed the pseudo-second-order kinetic model. And the rate-limiting step was intraparticle diffusion step. The most suitable eluent for CPX desorption was determined as phosphate buffer solution rather than ethanol, and NaCl solution. It desorbed the 100% of CPX solution in 5h.
Keywords: Ciprofloxacin; Adsorption; SiO2; Chitosan; Magnetic materials; MESOPOROUS CARBON; ACTIVATED CARBON; GRAPHENE OXIDE; WASTE-WATER; ADSORPTION; CIPROFLOXACIN; ADSORBENT; KINETICS; MICROSPHERES; TETRACYCLINE